Upaya Meningkatkan Kemampuan Menyusun Butir Soal Bagi Guru Kelas Melalui Workshop - Baiq Srijali (Journal of Classroom Action Research, 2022)
The ability to compile still low problem points can be overcome by academic coaching through workshops in schools with mentoring. This school action research aims to improve the ability of classroom teachers in State Elementary School 2 Perampuan in compiling problem points. The school's action research technique is carried out by carrying out an evaluation of the initial condition by assessing the repeat questions made by the classroom teacher, conducting problem-solving discussions, and continued with the implementation of actions, namely with workshops and ending with the evaluation of results. Data obtained by the author of the assessment of the question item before the action is carried out and after the action using the assessment instrument of the preparation of the problem item. The results of the assessment of the problem point are designed and on average so that it is known that there is an increase in the ability to compile the point of the class teacher in State Elementary School 2 Dispossession, except with the instrument of assessment of data points obtained by observations, interviews and notes made by the author during the implementation of the study. Based on the analysis of data from school action research results obtained the fact that there is a relationship between the workshop and the improvement of the ability to compile problem points, namely through the workshop can improve the ability of the classroom teacher in compiling problem points.